SISTEM AKUNTANSI PENGGAJIAN DAN PENGUPAHAN - Husnul Hasanah Hasibuan; Selly Puja Panca Rizky; Emiya Timanta Br Pinem (At-Tanmiyah Jurnal Ekonomi dan Bisnis Islam, 2024)
The payroll and wage accounting system is an essential component in supporting operational effectiveness, accurate record-keeping, and organizational accountability. This paper discusses the definition, objectives, benefits, documents, records, procedures, and internal controls involved in payroll and wage systems. The results of the discussion show that an effective payroll system not only ensures accurate and timely salary payments but also functions as an internal control mechanism to prevent fraud, errors, and manipulation. The use of documents such as attendance cards, time cards, payroll lists, and pay slips, along with accounting records such as payroll journals and general ledgers, plays an important role in producing accurate and auditable financial information. The payroll procedures—comprising attendance recording, salary calculation, validation, payment, and reporting—must be carried out sequentially and properly authorized. Internal controls, including segregation of duties, layered authorization, pre-numbered documents, and independent verification, are crucial to maintaining the integrity and security of the payroll process. This study concludes that a structured payroll and wage accounting system supported by information technology enhances efficiency, transparency, and employee trust in the organization. Keywords: accounting system, payroll, wages, internal control, payroll documents.